PRINSIP-PRINSIP EKONOMI ISLAM DALAM MENGHADAPI PERSOALAN EKONOMI KONTEMPORER - Suryani, Eli (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
Islam as a theory (religion) is an integral and totality. Islam have an economic system that is fundamentally different from the conventional economic system. It has its roots in the shari’a that shape the world view (world view) as well as strategic objectives (maqasid al-shari’a) which different from the secular system. Islamic theory construct it concept with mainstream of happiness (falah) and the good life (hayaatan tayyibah) which really emphasize brotherhood (ukhuwah) and the values of humanism, justice, socio-economic, and fulfillment of spiritual human needs. For that in problems of economics, Islam build principles: Tawhid, khilafah, terms of reference and framework, universal brotherhood, the resource is a responsibility from Allah, human happiness, brotherhood, and justice. With those principles that built would be able to construct a happy prosperous life in the world and the hereafter.